Sunshine on Leith - Englishby, Paul; Flemyng, Jason; Greenhorn, Stephen; Guthrie, Kevin, 1988-; Horrocks, Jane, 1964-; MacKay, George, 1992-; Mavor, Freya; Mullan, Peter; Thomas, Antonia, 1986- (2013)
Dexter Fletcher directs this cinematic adaptation of the acclaimed stage musical featuring the music of Scottish band The Proclaimers. Returning home from their most recent stint in Afghanistan, Davy (George MacKay) and Ally (Kevin Guthrie) have a new appreciation for life after witnessing the horrors of war first-hand. While Ally plans his proposal to Davy's sister Liz (Freya Mavor), Davy falls for Yvonne (Antonia Thomas) and the two couples come together in time for Liz's parent's wedding anniversary, but not everything is plain sailing for love in Leith ...